Infant and Adult Language Experience Can Differ in More than One Way: Reply to Arnon (2018). Issue 1 (2nd January 2020) - Hudson Kam, Carla L.
ABSTRACT: Hudson Kam (2018) examined whether learning of a particular aspect of language that adults are known to have difficulty with (grammatical gender) could be improved by manipulating the learning experience of adults so that it was more like that of infants. Specifically, based on likely differences between adult and child learners' experiences as well as theoretical assumptions about the nature of child first language learning, experimental participants initially heard spoken sentences without any accompanying meaning. This was an attempt to restrict learners' focus to the phonological aspects of the language, thereby facilitating category formation and, in turn, the learning of the behavior of the classes. However, the manipulation did not lead to improved learning. Arnon (2018) presented a critique of the study, based in part on differences between my results and her own in related studies. In this response, I discuss two main points raised in her critique: the nature of early language experience in infants in the study and sample size issues. I also examine what people were actually tasked with learning in my study and hers, as a way of explaining differences between our results.